Molecular Identification and Characterization of a Genotype 3 Hepatitis E Virus (HEV) Strain Detected in a Wolf Faecal Sample, Italy - Vittorio Sarchese; Paola Fruci; Andrea Palombieri; Federica Di Profio; Serena Robetto; Carlo Ercolini; Riccardo Orusa; Fulvio Marsilio; Vito Martella; Barbara Di Martino (Animals, 2021)
Hepatitis E virus (HEV) infection is a major health problem worldwide. In developed countries, zoonotic transmission of HEV genotypes (Gt) 3 and 4 is caused by the ingestion of raw or undercooked meat of infected pigs and wild boars, the main reservoirs of HEV. However, additional animals may harbour HEV or HEV-related strains, including carnivores. In this study, we investigated the molecular epidemiology of orthohepeviruses in wild canids by screening a total of 136 archival faecal samples, collected from wolves (42) and red foxes (94) in Northwestern Italy. Orthohepevirus RNA was identified in a faecal specimen, collected from a wolf carcass in the province of La Spezia (Liguria Region, Italy). The nearly full-length (7212 nucleotides) genome of the strain HEV/81236/Wolf/2019/ITA (GenBank accession no. MZ463196) was determined by combining a sequence-independent single-primer amplification (SISPA) approach with the Oxford Nanopore Technologies sequencing platform. Upon phylogenetic analysis, the HEV detected in wolf was segregated into clade HEV-3.1, displaying the highest nucleotide (nt) identity (89.0–93.3%) to Gt3 strains belonging to subtype c. Interestingly, the wolf faecal sample also contained porcine astrovirus sequences, endorsing the hypothesis of a dietary origin of the HEV strain due to preying habits.